116 The Obesity Paradox in Type II Diabetes Mellitus. Impact of Body Mass Index on Prognosis. (31st May 2014) - Costanzo, Pierluigi; Pellicori, Pierpaolo; Cleland, John; Clark, Andrew; Hepburn, David; Kilpatrick, Eric; Zhang, Jufen; Perrone-Filardi, Pasquale; Atkin, Stephen
Abstract : Background: Obese patients with type two diabetes mellitus (T2DM) may have a better prognosis than patients of normal weight, but reports are limited by study size, duration and confounders. Methods: We investigated the relationship between body mass index (BMI) and prognosis in 10, 568 patients with T2DM without known CV disease followed for a median of 10.6 (IQR: 7.8–13.4) years. Hospital admissions for acute coronary syndrome (ACS), cerebrovascular accidents (CVA) and heart failure (HF) and all-cause mortality were recorded. Information on comorbidity (cancer, lung diseases and chronic renal failure) was also collected as confounder. Results: Median age was 63 ± 19 years, 54% were men and median BMI was 28.8 (IQR: 25.2–32.4 kg.m 2 ). Adjusting for differences in age and other variables, patients in the highest quartile of BMI had the greatest risk of hospitalisation for ACS or HF (HRs with 95% CI for highest versus lowest quartile were 1.39 1.14–1.70; p = 0.001 and 1.36 1.08–1.71; p = 0.01 respectively) but the risk of CVA was similar amongst BMI quartiles. However, patients in higher BMI quartiles had lower mortality rates, with the nadir of risk at BMI 25–30 kg/m 2 (adjusted for confounders). Greater BMI was associated with lower mortality especially amongst older patients. Conclusions: Patients with T2DM and moderately increased BMI, in the overweight range of 25–30 kg/m 2, have a lower mortality than slimmer patients. Amongst older patients, even higher BMI may be associated with lower risk. However, obesity is associated with an increased risk of hospitalisation for cardiovascular events.